Less Invasive Management of Endovascular Embolization and Neuroendoscopic Surgery for a Dural Arteriovenous Fistula Presenting with Acute Subdural Hematoma - Ishibashi, Ryota; Maki, Yoshinori; Ikeda, Hiroyuki (Asian Journal of Neurosurgery, 2022)
Acute subdural hematoma (ASDH), which causes midline shift of the brain, rarely arises from a dural arteriovenous fistula (DAVF). Herein, we report the first case of a DAVF manifesting ASDH, which was treated less invasively with endovascular embolization of a drainer of the DAVF and hematoma removal under neuroendoscopy. A 59-year-old man with a sudden onset of headache was transported to our hospital. Left ASDH and intracerebral hematoma in the left occipital lobe were detected. A cerebral angiogram revealed a DAVF fed by the petrosquamous branch of the left middle meningeal artery and jugular branch of the right ascending pharyngeal artery. The shunting point in the lateral tentorial DAVF drains through the internal occipital vein to the superior sagittal sinus. A varix was recognized in the draining vein (Borden type 3, Cognard type 4). The DAVF was embolized with Onyx (Medtronic, Minnesota, USA), and the left ASDH was removed with a small craniotomy under neuroendoscopy. No origin of the left ASDH was apparent in the surgical field. The patient was discharged from the hospital on postoperative day 18. The patient's status was modified Rankin scale 1 on discharge. Our management of combined endovascular treatment and neuroendoscopic hematoma removal may be useful and less invasive for hemorrhagic DAVF.
Keywords: dural arteriovenous fistula; endovascular; Onyx; neuroendoscope; acute subdural hematoma